Unconditional Love Reflected In Steve Marra's Amanda Movie (2009) : An Individual Psychological Approach - Ningrum, Norma Pratiwi Mustika, Drs. H. Abdillah Nugroho, M.Hum, Nur Hidayat, S.Pd (2013)
The research is proposed to analyze how the unconditional love reflected in Amanda movie 2009 by Individual Psychological Approach. There are two objectives: the first is to analyze the movie in term of structural elements, and the second is to analyze the movie based on the individual Psychological Perspective. This study is a qualitative study, using Steve Marra's Amanda movie 2009 as of structural elements, and the secondary data. The primary data source is Amanda movie which is directed by Steve Marra, and the secondary data are some articles, book of literary and internet related to the subject. The method of collecting data in this research is library research by watching the movie, reading some related books and articles, accessing internet, taking notes of important part, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows that the movie illustrates how to get unconditional love, it proves that love has no gender, true love is unconditional. Getting unconditional love is not easy, but if it can be gotten, it will make happy for everyone in their relationship.